Krakow : cztery pory roku w fotografii Henryka Hermanowicza - Hermanowicz, Henryk; Banach, Jerzy (Krakow : Wydawn. Literackie, 1979)
A photographic guide of the city of Krakow, Poland's old capitol.
Summaries in English, French, German, and Russian.
List of illustrations and legends also in English, French, German, and Russian.
Keywords: Krakow (Poland) -- Pictorial works